Analisis Pengaruh Pertumbuhan Ekonomi, Jumlah Industri, Penanaman Modal Asing Dan Kemiskinan Terhadap Emisi Co2 Di Indonesia - Fiza Zainur Putri; Kasman Karimi; Mukhlizul Hamdi; Bakaruddin Bakaruddin; Norra Isnasia Rahayu (Akuntansi & Ekonomika, 2022)
CO2 emission is a serious problem that has a direct impact on the environment. Therefore, this paper aims to examine the short-term and long-term effects on the variables of economic growth (GDP), number of industries (JI), foreign investment (FDI) and poverty (KM) on CO2 emissions in Indonesia. This study uses an analysis of the Error Correction Model (ECM) method in the period 1995 to 2019. The empirical results show that the GDP, JI and FDI variables have a significant effect on CO2 emissions while the KM variable has no significant effect on CO2 emissions in both the short and long term in 1995-2019 in Indonesia.